Fair, Individually Rational and Cheap Adjustment - Polevoy, Gleb; Dziubiński, Marcin (Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence)
Consider the practical goal of making a desired action profile played, when the planner can only change the payoffs, bound by stringent constraints. Applications include motivating people to choose the closest school, the closest subway station, or to coordinate on a communication protocol or an investment strategy. Employing subsidies and tolls, we adjust the game so that choosing this predefined action profile becomes strictly dominant. Inspired mainly by the work of Monderer and Tennenholtz, where the promised subsidies do not materialise in the not played profiles, we provide a fair and individually rational game adjustment, such that the total outside investments sum up to zero at any profile, thereby facilitating easy and frequent usage of our adjustment without bearing costs, even if some players behave unexpectedly. The resultant action profile itself needs no adjustment. Importantly, we also prove that our adjustment minimises the general transfer among all such adjustments, counting the total subsidising and taxation.
Keywords: adjustment; strictly dominant; fairness; individually rational; transfer; tax; subsidy

Die professionelle pädagogische Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften: Belastungsfaktor oder Ressource? - Kärner, Tobias; Goller, Michael; Bonnes, Caroline; Maué, Elisabeth (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung: Der Beitrag befasst sich mit der professionellen pädagogischen Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften, deren Beitrag für die Beanspruchung der Referendar*innen bisher noch nicht eingängig untersucht wurde. Das Ziel der Studie ist es, anhand einer Querschnittserhebung von 2583 Referendar*innen und ausgebildeten Lehrkräften, kompensatorische sowie verstärkende Effekte der Beziehungsdimensionen Transparenz, Fairness, Vertrauen und Ambivalenz auf die wahrgenommene Beanspruchung im Referendariat zu untersuchen. Die Analyse erfolgt mittels eines latent moderierten Strukturgleichungsansatzes. Die Ergebnisse zeigen, dass Belastungen durch die Kerntätigkeiten im Referendariat sowie Belastungen durch den Umgang mit Kolleg*innen im Lehrer*innenkollegium in signifikant positivem Zusammenhang mit resultierenden Beanspruchungsreaktionen stehen. Je transparenter, fairer und vertrauensvoller und je weniger ambivalent die Beziehung zur Seminarlehrkraft erlebt wird, desto geringer fallen die Beanspruchungsreaktionen aus. Die Ergebnisse werden hinsichtlich ihrer Relevanz für die Beziehungsarbeit im Referendariat als zentralem Ausbildungsbestandteil der zweiten Phase der Lehrer*innenausbildung diskutiert.
Keywords: Education

Cardinality Constrained Scheduling in Online Models - Epstein, Leah; Lassota, Alexandra; Levin, Asaf; Maack, Marten; Rohwedder, Lars (39th International Symposium on Theoretical Aspects of Computer Science, STACS 2022, March 15-18, 2022, Marseille, France (Virtual Conference))

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

"Mama Always Had a Way of Explaining Things So I Could Understand": A Dialogue Corpus for Learning How to Explain - Wachsmuth, Henning; Alshomary, Milad (Proceedings of the 29th International Conference on Computational Linguistics)

On the Role of Knowledge in Computational Argumentation - Lauscher, Anne; Wachsmuth, Henning; Gurevych, Iryna; Glavaš, Goran (Transactions of the Association for Computational Linguistics)

Identifying the Human Values behind Arguments - Kiesel, Johannes; Alshomary, Milad; Handke, Nicolas; Cai, Xiaoni; Wachsmuth, Henning; Stein, Benno (Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics)

Domain-specific Language for Condition Monitoring Software Development - Pasic, Faruk; Becker, Matthias (2022 IEEE 27th International Conference on Emerging Technologies and Factory Automation (ETFA))

"Swer siner kunst meister ist, der hat gewalt an siner list". Herborts von Fritzlar Liet von Troye als Fortsetzungstext des Eneasromans Heinrichs von Veldeke am Schnittpunkt von Aneignung und Neukonstitution - Somogyi, Peter (Troja bauen)

No Word Embedding Model Is Perfect: Evaluating the Representation Accuracy for Social Bias in the Media - Spliethöver, Maximilian; Keiff, Maximilian; Wachsmuth, Henning (Proceedings of The 2022 Conference on Empirical Methods in Natural Language Processing (EMNLP 2022))
News articles both shape and reflect public opinion across the political spectrum. Analyzing them for social bias can thus provide valuable insights, such as prevailing stereotypes in society and the media, which are often adopted by NLP models trained on respective data. Recent work has relied on word embedding bias measures, such as WEAT. However, several representation issues of embeddings can harm the measures' accuracy, including low-resource settings and token frequency differences. In this work, we study what kind of embedding algorithm serves best to accurately measure types of social bias known to exist in US online news articles. To cover the whole spectrum of political bias in the US, we collect 500k articles and review psychology literature with respect to expected social bias. We then quantify social bias using WEAT along with embedding algorithms that account for the aforementioned issues. We compare how models trained with the algorithms on news articles represent the expected social bias. Our results suggest that the standard way to quantify bias does not align well with knowledge from psychology. While the proposed algorithms reduce the~gap, they still do not fully match the literature.

Pfirsichbaum und dunkler Wald. Pflanzliche Konfigurationen zwischen Dynamisierung und Innehalten in 'Partonopier und Meliur' Konrads von Würzburg - Musiol, Marie-Luise; Winst, Silke (Spiritual Vegetation: Vegetal Nature in Religious Contexts Across Medieval and Early Modern Europe (Berliner Mittelalter- und Frühneuzeitforschung, Vol. 26))

Bennewitz, Ingrid/Eming, Jutta/Traulsen, Johannes: Gender Studies – Queer Studies – Intersektionalität. Eine Zwischenbilanz aus mediävistischer Perspektive (Berliner Mittelalter- und Frühneuzeitforschung 25), Göttingen 2019 - Musiol, Marie-Luise (Sexuologie)

Menschlicher Körper, heiliger Körper. Zur Kreuzigung Christi im Donaueschinger Passionsspiel - Musiol, Marie-Luise (Unverfügbar. Kulturen des Heiligen)

Overview of Touché 2022: Argument Retrieval - Bondarenko, Alexander; Fröbe, Maik; Kiesel, Johannes; Syed, Shahbaz; Gurcke, Timon; Beloucif, Meriem; Panchenko, Alexander; Biemann, Chris; Stein, Benno; Wachsmuth, Henning; Potthast, Martin; Hagen, Matthias (Lecture Notes in Computer Science)

Augmented Reality Anwendungen in der betrieblichen Aus‐ und Weiterbildung - Kärner, Tobias; Goller, Michael; Maier, Andreas (Digitalisierung und digitale Medien in der Berufsbildung: Konzepte, Befunde und Herausforderungen)
Der Beitrag widmet sich dem Einsatz von Augmented Reality (AR) in betrieblichen Aus- und Weiterbildungskontexten. Hierbei stehen insbesondere Fragen zu Berufsfeldern und Ausbildungsinhalten, zu verwendeten AR-Spezifikationen, zu Zusammenhängen zwischen AR-Anwendung und leistungs-, wahrnehmungs- und motivationsbezogenen Variablen sowie zur didaktischen Einbettung entsprechender Technologien im Fokus. Auf Basis einer integrierenden Sichtung bestehender Literatur konnten insgesamt 16 Studien sowie zwei bereits vorliegende Literaturreviews in die Analyse eingeschlossen werden. Die Ergebnisse verweisen u. a. auf eine heterogene Lage hinsichtlich forschungsmethodischer Zugänge und didaktischer Referenzkonzepte. Weitgehend förderliche Effekte auf leistungs-, wahrnehmungs- und motivationsbezogene Variablen stimmen insgesamt bezüglich des AR-Einsatzes positiv, machen aber auch die Notwendigkeit einer integrierten Betrachtung technologischer und pädagogisch-instruktionaler Gestaltungsparameter deutlich.
Keywords: Augmented Reality; Ausbildung; Weiterbildung; Lernen mit digitalen Medien; integratives Literaturreview

Kompetenzen des betrieblichen Ausbildungspersonals: Eine literaturbasierte Systematisierung - Bonnes, Caroline; Binkert, Julia; Goller, Michael (Berufsbildung in Wissenschaft und Praxis – BWP)
Startpunkt jeglicher Professionalisierungsbemühungen ist ein Verständnis der für das professionelle Handeln notwendigen Kompetenzen. Dieser Beitrag widmet sich der literaturbasierten Identifikation von Kompetenzen des betrieblichen Ausbildungspersonals und ordnet diese den vier Kompetenzbereichen Fach-, Methoden-, Sozial- und Selbstkompetenz zu. Die Ergebnisse können sowohl als Grundlage für weitere Forschung dienen als auch in der Praxis als Orientierung für die Gestaltung von Qualifizierungsmaßnahmen verwendet werden.

Argument Novelty and Validity Assessment via Multitask and Transfer Learning - Alshomary, Milad; Stahl, Maja (Proceedings of the 9th Workshop on Argument Mining)
An argument is a constellation of premises reasoning towards a certain conclusion. The automatic generation of conclusions is becoming a very prominent task, raising the need for automatic measures to assess the quality of these generated conclusions. The SharedTask at the 9th Workshop on Argument Mining proposes a new task to assess the novelty and validity of a conclusion given a set of premises. In this paper, we present a multitask learning approach that transfers the knowledge learned from the natural language inference task to the tasks at hand. Evaluation results indicate the importance of both knowledge transfer and joint learning, placing our approach in the fifth place with strong results compared to baselines.

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry